The Legal Nature of the Sports Sponsorship Contract - Hasoony, Mohammed; Abdel Reda, Hussein (Journal of Legal Sciences, 2023)
The sports sponsorship contract is one of the most important contracts concluded by sports institutions in order to obtain sufficient funding for the performance of its activities. Contract and its development.This study dealt with the legal nature of the sports sponsorship contract by examining the extent to which some of the provisions of the named contracts apply to it, and then applying the provisions of which one will apply to it, by dealing with the contracts on the benefit such as the licensing contract, the deposit contract, and the contracts on work such as the work contract and the contracting contract.